1997
DOI: 10.1093/hmg/6.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Syrian hamster cardiomyopathy gene

Abstract: The BIO14.6 hamster is a widely used model for autosomal recessive cardiomyopathy. These animals die prematurely from progressive myocardial necrosis and heart failure. The primary genetic defect leading to the cardiomyopathy is still unknown. Recently, a genetic linkage map localized the cardiomyopathy locus on hamster chromosome 9qa2.1-b1, excluding several candidate genes. We now demonstrate that the cardiomyopathy results from a mutation in the delta-sarcoglycan gene that maps to the disease locus. This mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(137 citation statements)
references
References 37 publications
2
134
0
1
Order By: Relevance
“…11 Similar to the animal models for d-sarcoglycan-deficiency, the cardiomyopathic hamster models and the d-sarcoglycan knock-out mouse, patients can already present severe cardiomyopathy at young age in addition to muscular dystrophy. 23,24 Cardiomyopathy is not a core component of LGMD2F and there have been reports of several patients without cardiac involvement. 25 On the other hand, it has been suggested that mutations in the SGCD gene may cause autosomal-dominant DCM independently from symptoms of LGMD.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar to the animal models for d-sarcoglycan-deficiency, the cardiomyopathic hamster models and the d-sarcoglycan knock-out mouse, patients can already present severe cardiomyopathy at young age in addition to muscular dystrophy. 23,24 Cardiomyopathy is not a core component of LGMD2F and there have been reports of several patients without cardiac involvement. 25 On the other hand, it has been suggested that mutations in the SGCD gene may cause autosomal-dominant DCM independently from symptoms of LGMD.…”
Section: Discussionmentioning
confidence: 99%
“…All the CM hamsters share the genomic deletion of about 30-kb interval, which includes the two promoters and first exons of delta-sarcoglycan gene with consequent loss of its protein product [212,248,249]. The consequences of the genetic loss of delta-sarcoglycan in heart are related not only to sarcolemmal fragility but also to coronary vasospasm from disruption of dystrophin-associated protein complex [44].…”
Section: Syrian Cardiomyopathic Hamstermentioning
confidence: 99%
“…The cardiomyopathy Syrian hamster Bio14.6 26 was the first available LGMD 2F animal model, with a large deletion in its d-sarcoglycan gene. 27,28 The genetic mutation causes biochemical deficiency of the entire SG complex on both skeletal and cardiac muscle cell membranes. In addition to skeletal muscle myopathy, the Bio14.6 hamsters also suffer from severe cardiomyopathy and congestive heart failure, a primary cause of premature death.…”
Section: Introductionmentioning
confidence: 99%